Design and Evaluation of Automated Fluid-Transfer Suction Pump Based on Arduino for Thoracic Trauma Applications - Fuad Afandi; Radian Indra Mukromin; Yanuar Mukhammad; Rahma Ajeng Puspitasari (G-Tech: Jurnal Teknologi Terapan, 2026)
Thoracic trauma frequently leads to the accumulation of air or fluid within the pleural cavity, compromising pulmonary expansion and requiring immediate evacuation through suction systems. Conventional suction pumps rely heavily on continuous manual monitoring to prevent container overflow, creating potential risks of backflow, contamination, or device malfunction. This study aims to design and evaluate an automated dual-container suction pump prototype capable of maintaining stable suction pressure while minimizing manual supervision during fluid evacuation. The proposed system employs an Arduino Uno microcontroller and integrates an MPX5700DP pressure sensor for suction monitoring, an E18-D80NK infrared sensor for full-container detection, a 12 V solenoid valve for automated flow diversion, a 25DA Solid State Relay (SSR) for safe power switching, and a buzzer alarm for emergency shutdown. Experimental results indicate that all electrical outputs remain within acceptable tolerance ranges (1.2–4.7%), and suction pressure is consistently maintained at 70 cmHg before and after system modification. The accuracy of infrared sensor achieved a detection accuracy of only 30%, highlighting its limited suitability for reliable medical fluid-level monitoring and underscoring the need for alternative sensing technologies in future implementations. Despite this limitation, the prototype demonstrates the feasibility of automated fluid-transfer control and provides a practical foundation for the development of safer and more reliable suction systems for thoracic trauma applications.